Law and religion as a strategy in favor of profitable cultural osmosis: a wide look to civil law systems (Stato, Chiese e pluralismo confessionale, 2018)
SUMMARY: 1. Together in diversity: law and religion in modern civil law systems - 2. The religious traditions in law and religion - 3. The religion and law osmosis in law-making processes - 4. The religion and law osmosis in jurisdiction - 5. As a strategy: the nomopoietic function of religions in the legal koinè.